Implementasi metode EOQ dalam upaya efisiensi persediaan bahan baku pada pembuatan simping di UMKM SNS Purwakarta - Puspasari, Dewi; Pamungkas, Eko Wiji (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2025)
SNS is a micro, small, and medium enterprise (MSME) located in Purwakarta Regency, West Java, which operates in the snack manufacturing business sector, namely Simping. Simply put, SNS often experiences obstacles in carrying out the production process, namely that the business owner still has difficulty calculating the number of raw materials needed and the materials that must be ordered. The implementation of the EOQ method in SNS MSMEs can be concluded that from several types of raw materials used in the process of making stamping, it can be calculated for the primary raw materials which have the most widely used quantities, namely tapioca flour, wheat flour, cooking oil and garlic with using the EOQ method, the respective EOQ for tapioca flour is 147.3 kg, wheat flour is 104.14 kg, cooking oil is 74 kg and garlic is 52 kg. In comparison, tapioca flour is 77kg for safety stock; wheat flour is 19.25kg, 4.8 kg of cooking oil, and 1.2 kg of garlic. The reorder point for each raw material is tapioca flour at 6.37kg, wheat flour at 3.18kg, cooking oil at 1.59kg, and garlic at 0.8kg.